Efficient Enrichment of Chiral β-Sulfonyl Ketones through Asymmetric β-Elimination - Liu, Yidong; Qin, Wenling; Yan, Hailong (Synlett, 2016)
Chiral sulfones are important functionalities of various interesting organic compounds. Herein we reported a catalytic enantioselective β-elimination reaction for the first time and realized the kinetic resolution of racemic β-sulfonyl ketones. The resulted enones could be recovered to re-perform the catalytic resolution. This protocol overcame the yield limitation of 50% of resolution procedures. The resulting chiral β-sulfonyl ketones were successfully transformed into corresponding amide, hydrazine, and alcohols with good stereocontrol, demonstrating the application prospect of this reaction system.
Keywords: enantioselective β-elimination; chiral sulfone; kinetic resolution